eLingua : Issue 1 : Jan 2021 / Academy of Language Studies - Marimuthu, Rasaya; Giap, Lim Soo; Ismail, Rushita; Ab Rahim, Suzana; Razali, Wan Noorli; Mohd Yusoff, Noor Laili; Fen, Ong Sheau (Academy of Language Studies, 2021)
1. Covid 19 Challenges & Opportunities: UiTMCPP- UNTAN Webinar 2020 2. Open Distance Learning (ODL) Workshops of Academy of Language Studies, UiTMCPP 3. Asyura - Its Religious & Cultural Celebration 4. International Conference on Environmental and Technology of Law, Business and Education 2020 5. KEJOHANAN TENPIN BOLING ANTARA BAHAGIAN PIALA REKTOR UiTM CAWANGAN PULAU PINANG 2020 6. Program Literasi untuk Kanak-kanak Tabika Kemas Kampung Tok Elong 7. ‘Getting to know you more ’Professor Ts Dr Salmiah Kasalong Rector, UiTMCPP 8. Jom kenali IJPTL: Jurnal ‘kasih sayang’ 9. Penulisan Surat Rasmi Menjadi Punca Stres 10. Every Author Needs an Editor, Don't You? 11. English Language Club AGM 2020 12. ENGLISH CLUB E-POSTER COMPETITION (NOV-DEC 2020) 13. ENGLISH CLUB SHORT ESSAY COMPETITION (NOV 2020) 14. APB Greenation Buddies @ UiTMCPP 15. It’s brow, bro! 16. Useful Tips in Teaching Online Effectively 17. Penggunaan Kata Sendi ‘Zai’ dalam Bahasa Mandarin 18. Are you having fun learning French? 19. Ritualistic Dances in Malaysia 20. Oh, my face! Goodbye chemicals, hello facial oils! 21. Sugar Gliders 22. Rpsa (Part 1) 23. Self-love first 24. ‘The Lesson I Learnt from My Childhood Experience’ ELC030 (Pre-Diploma English) Semester Oct 2020 - Feb 2021 25. French in Linguistic Landscape 26. Conquering the Mount Kinabalu - My personal account (19.02.2020 - 23.02.2020) 27. PELAJARAN MAMPU MENGUBAH MASA DEPAN KYOIKU WA MIRAI WO HENKOU SURU KOTO 28. lecturer's Contribution 29. ACHEH: 15 TAHUN SELEPAS TSUNAMI KRISMAS*